Исследование механической очистки ливневых стоков, образованных на объектах автомобильно-дорожного комплекса - Юрченко, В. А.; Мельникова, О. Г.; Бахарева, Анна Юрьевна; Ячник, М. В. (Технологический центр, Украинский государственный университет железнодорожного транспорта, 2015)
В экспериментальных исследованиях установлено, что концентрация нефтепродуктов в поверхностных сточных водах, образующихся на объектах автомобильно-дорожного комплекса, многократно превышает ПДК для сброса в водные объекты. В ливневых стоках с территорий АЗС и автостоянок концентрация нефтепродуктов более высокая, чем в ливневых стоках с автодорог, и в их составе преобладают условно тяжелые фракции нефтепродуктов, более эффективно удаляемые при отстаивании.

Experimental research revealed that the concentration of oil products in surface wastewater, formed in winter and summer on the objects of automobile and road complex – gas stations, car parks and roads, greatly exceeds the MPC for discharge into water bodies. In stormwater runoffs at gas stations and car parks, the concentration of oil products has higher values than in surface wastewater, formed on the roads, despite the low traffic level. In surface wastewater, formed at gas stations and car parks, conditionally heavy fractions of oil products, more efficiently removable during settling prevail. The effect of surface wastewater treatment from oil products (maximum 80 %) depends on several parameters, the most significant of which is the concentration of suspended solids.
Research of mechanical treatment of stormwater runoffs formed on objects of automobile and road complex
Keywords: автомобильно-дорожный комплекс; объекты дорожной инфраструктуры; ливневые стоки; механическая очистка; нефтепродукты; automobile and road complex; objects of road infrastructure; stormwater runoffs; mechanical treatment; oil products